2010
DOI: 10.1016/j.ijsolstr.2010.09.002
|View full text |Cite
|
Sign up to set email alerts
|

On shear correction factors in the non-linear theory of elastic shells

Abstract: a b s t r a c tTheoretical values of two correction factors a s = 5/6 and a t = 7/10 are established for the respective transverse shear stress resultants and stress couples within the general, dynamically and kinematically exact, six-field theory of elastic shells. These values do not depend on the shell material symmetry, geometry of the base surface, the shell thickness, or any kind of kinematic and/or dynamic constraints. The analysis is based on the complementary energy density following from the transver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 46 publications
0
70
0
Order By: Relevance
“…[30,31]). The overall two-dimensional field equation is obtained by an integration, but the concerned two-dimensional variable likeS (andx in a dynamic system) in (3.14) 1 is treated as a whole instead of being expanded in series.…”
Section: Remarkmentioning
confidence: 99%
“…[30,31]). The overall two-dimensional field equation is obtained by an integration, but the concerned two-dimensional variable likeS (andx in a dynamic system) in (3.14) 1 is treated as a whole instead of being expanded in series.…”
Section: Remarkmentioning
confidence: 99%
“…Hence, the deformations of the micropolar plate or shell are described by the translation vector v and the rotation vector θ which are defined at the base surface M. Using the direct approach the basics of the linear theory of micropolar shells are summarized in [Eremeyev and Zubov 2008;; see also Appendix D in [Eremeyev et al 2013]. The governing equations of the micropolar shells and plates coincide with the relations of the general 6-parameter nonlinear shell theory presented in [Chróścielewski et al 2004;Libai and Simmonds 1998] in the case of small deformations derived using the through-the-thickness integration procedure.…”
Section: Micropolar Plate and Shell Equationsmentioning
confidence: 99%
“…Obviously, in this theory of shells the action of the drilling moment M α3 is taken into account. For example, such possibility may be useful to describe the interaction of the shell and the rigid body or for the description of the deformations of multifolded plates, see [Chróścielewski et al 2004]. The static and kinematic boundary conditions take the form…”
Section: Micropolar Plate and Shell Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extending an approach previously used for the composite beams, Nguyen et al (2008) proposed shear correction factors for the power-law FGM plates using the shear strain energy equivalence method. Chróścielewski, et al (2010) suggested using two shear correction factors for the geometrically nonlinear elastic regular and irregular shells. Menaa et al (2012) used a concept similar to Nguyen et al (2008), but presented an expression for plates made of sigmoid-law functionally graded materials.…”
Section: Introductionmentioning
confidence: 99%